El historiador y el general: imposiciones y disensos en torno a la interpretación pública de la historia en Paraguay - Liliana M. Brezzo (Nuevo mundo - Mundos Nuevos, 2014)
This study investigates the politics of history outspoken government of General Alfredo Stroessner in Paraguay, taxation mechanisms and dissent. This historiographical trend called revisionism built by Paraguayan historian Juan E. O'Leary to show the process by which he became the Stroessner regime support is analyzed. At the same time attention is on the run, in the confines of the state, scholars associated with the Paraguayan Institute of Historical Research and the National University of Asuncion.